The Implementation of Problem Based Learning Model Assisted by Scaffolding Method to Improve Students' Communication Ability at SMA Negeri 4 Palu - Layukan, Surini; Non Shamdas, Gamar Binti; Erwin, Muhammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to describe and evaluate the effectiveness of the implementation of problem based learning model assisted by scaffolding method to improving students' communication ability at SMA Negeri 4 Palu. The research used a classroom action approach implemented in two cycles with stages of planning, implementation, observation, and reflection. The research instrument used consists of a test containing three essay questions to measure written communication ability and observation sheet to measure oral communication ability, which are analyzed using descriptive methods. The total score percentage of students' oral communication ability in cycle I (73%) and cycle II (76%), an increase of (3%), with an average score of (75%) in the high category, while the total score percentage of students' written communication ability in cycle I (76%) and cycle II (80%), an increase of (4%), with an average score of (78%) in the high category. Based on the research results, it is concluded that the application of the problem based learning model assisted by the scaffolding method is very effective in enhancing students' communication ability both orally and in writing.